Quantitative Proteomic Analysis of BHK-21 Cells Infected with Foot-and-Mouth Disease Virus Serotype Asia 1. - Hui-Chen Guo; Ye Jin; Shi-Chong Han; Shi-Qi Sun; Yan-Quan Wei; Xian-Ji Liu; Xia Feng; Ding Xiang Liu; Xiang-Tao Liu (PLoS ONE)
Stable isotope labeling with amino acids in cell culture (SILAC) was used to quantitatively study the host cell gene expression profile, in order to achieve an unbiased overview of the protein expression changes in BHK-21 cells infected with FMDV serotype Asia 1. The SILAC-based approach identified overall 2,141 proteins, 153 of which showed significant alteration in the expression level 6 h post FMDV infection (57 up-regulated and 96 down-regulated). Among these proteins, six cellular proteins, including three down-regulated (VPS28, PKR, EVI5) and three up-regulated (LYPLA1, SEC62 and DARs), were selected according to the significance of the changes and/or the relationship with PKR. The expression level and pattern of the selected proteins were validated by immunoblotting and confocal microscopy. Furthermore, the functions of these cellular proteins were assessed by small interfering RNA-mediated depletion, and their functional importance in the replication of FMDV was demonstrated by western blot, reverse transcript PCR (RT-PCR) and 50% Tissue Culture Infective Dose (TCID50). The results suggest that FMDV infection may have effects on the expression of specific cellular proteins to create more favorable conditions for FMDV infection. This study provides novel data that can be utilized to understand the interactions between FMDV and the host cell.